2021
DOI: 10.1159/000519713
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiac Output Measurement by Electrical Velocimetry with Echocardiography in Extremely Low Birth Weight Neonates

Abstract: <b><i>Introduction:</i></b> Electrical velocimetry (EV) offers a noninvasive tool for continuous cardiac output (CO) measurements which might facilitate hemodynamic monitoring and targeted therapy in low birth neonates, in whom other methods of CO measurement are not practicably feasible. <b><i>Methods:</i></b> This prospective observational study compared simultaneous cardiac output measurements by electrical velocimetry (CO<sub>EV</sub>) with transt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Blohm et al ( 26 ) showed that PDA status showed a trend toward significance when TEBT was compared to TTE measured VTI mean bias ( p = 0.077) but not when TEBT was compared to TTE m-mode measurements. Hassan et al ( 35 ) showed a near doubling in mean CO bias between PDA and non-PDA measurements (−167 ml/min and −89 ml/min, respectively, p < 0.001).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Blohm et al ( 26 ) showed that PDA status showed a trend toward significance when TEBT was compared to TTE measured VTI mean bias ( p = 0.077) but not when TEBT was compared to TTE m-mode measurements. Hassan et al ( 35 ) showed a near doubling in mean CO bias between PDA and non-PDA measurements (−167 ml/min and −89 ml/min, respectively, p < 0.001).…”
Section: Resultsmentioning
confidence: 94%
“…Increased complexity of respiratory support intervention caused an increase in PE. Hassan et al ( 35 ) showed that HFV only had a significantly lower bias ( p = 0.002) as compared to IMV and CPAP.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations